Social Capital:Mediator of Citizens Behaviour and Public Accountability in Local Governments of Uganda (Global Journal of Management and Business Research, 2019)
Abstract not found
Keywords: citizens2019; behaviour; social capital; local governments; mediating effects; public accountability; Uganda